UNESCO Chair in Bioethics and Human Rights: 2010 Bioethics Art Competition - Denbina, Yvonne (Studia Bioethica, 2013)
This event was born on September 10, 2010 after a meeting with Alberto Garcia and Fr. Joseph Tham, LC. They are professors in bioethics and represented the UNESCO Chair in Bioethics and Human Rights. The question we considered was, “How to integrate the arts in the equation consisting of science, law and bioethics?”